Reading interest, confidence with text and reading performance of grade 4 public school pupils - Basadre, Pier Angeli Monderondo (2006)
The study aimed to investigate the relationship among reading interests, confidence with text, and reading performance of Grade 4 public school pupils. The pupils' level of reading interest was assessed based on their most preferred and least preferred titles of texts presented to them before actual reading. The Confidence with text Questionnaire was translated in Filipino to help the respondents comprehend. 30 public school pupils from 5 heterogeneous classes participated. Texts considered interesting by the pupils are those which address their individual preferences, need for information, and recreation. Texts not considered interesting are those with difficult words, scary or unpleasant topics/expressions and unappealing titles. It was recommended that teachers, administrators, policymakers, curriculum writers, storybook writers, and publishers work together to improve the pupils' reading interest, confidence with text and reading performance, particularly in expository texts.
Thesis (M.A. Reading Education)--University of the Philippines, Diliman.
Keywords: Reading interests -- Philippines -- Bulacan; Reading (Elementary) -- Philippines -- Bulacan; School children -- Rating of -- Philippines -- Bulacan